2007
DOI: 10.1289/ehp.9367
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Genistein Treatment in Mammary Gland, Uterus, and Vagina

Abstract: BackgroundThe isoflavone genistein (GEN) is found in soy (Glycine max) and red clover (Trifolium pratense). The estrogenic activity of GEN is known, and it is widely advertised as a phytoestrogen useful in alleviating climacteric complaints and other postmenopausal disorders. Knowledge of effects of long-term administration of GEN in laboratory animals is scarce, and effects in the uterus and mammary gland after long-term administration have not been studied. The uterus and mammary gland are known to be negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 50 publications
6
33
0
12
Order By: Relevance
“…It has been recently confirmed that progestogen exposure might negatively influence reproductive health, in terms of fertility and sexual differentiation [38]. Additionally, it is acknowledged that the uterus and mammal glands are negatively affected by the estrogens used in hormone therapy [39]. Through the present study, hormone administration to pregnant women was for the first time assessed and signifi- [40].…”
Section: Macrosomia Risk Factorsmentioning
confidence: 70%
“…It has been recently confirmed that progestogen exposure might negatively influence reproductive health, in terms of fertility and sexual differentiation [38]. Additionally, it is acknowledged that the uterus and mammal glands are negatively affected by the estrogens used in hormone therapy [39]. Through the present study, hormone administration to pregnant women was for the first time assessed and signifi- [40].…”
Section: Macrosomia Risk Factorsmentioning
confidence: 70%
“…Our observed effect of genistein on uterine weight is consistent with previous reports in the literature. For example, Rimoldi et al 28 showed in OVX rats that a 3-month oral regimen of genistein (54 mg=kg=day) significantly increased uterine weight. Our observed increase in femur weight was also in accord with previous studies demonstrating that genistein (administered for either 3 or 7 weeks) increased bone formation in OVX rats.…”
mentioning
confidence: 99%
“…The extract did not affect the lobuloalveolar and duct apparatus of the ovx rats whereas estradiol (E2) containing food resulted in a massive stimulation of the lobuli and duct (Fig. 3a-f ) [26]. Sprague-Dawley rats treated with DMBA developed typical mammary tumor structures that were inhibited by oral administration of an isopropanolic CR extract [27].…”
Section: Cimicifuga Racemosa (Black Cohosh)mentioning
confidence: 99%